A pleiotropic interaction between vision loss and hypermelanism in Astyanax mexicanus cave x surface hybrids - Gross, Joshua B. (BMC Evol Biol, 2016)
BACKGROUND: Cave-dwelling animals evolve various traits as a consequence of life in darkness. Constructive traits (e.g., enhanced non-visual sensory systems) presumably arise under strong selective pressures. The mechanism(s) driving regression of features, however, are not well understood. Quantitative trait locus (QTL) analyses in Astyanax mexicanus Pachón cave x surface hybrids revealed phenotypic effects associated with vision and pigmentation loss. Vision QTL were uniformly associated with reductions in the homozygous cave condition, however pigmentation QTL demonstrated mixed phenotypic effects. This implied pigmentation might be lost through both selective and neutral forces. Alternatively, in this report, we examined if a pleiotropic interaction may exist between vision and pigmentation since vision loss has been shown to result in darker skin in other fish and amphibian model systems. RESULTS: We discovered that certain members of Pachón x surface pedigrees are significantly darker than surface-dwelling fish. All of these “hypermelanic” individuals demonstrated severe visual system malformations suggesting they may be blind. A vision-mediated behavioral assay revealed that these fish, in stark contrast to surface fish, behaved the same as blind cavefish. Further, hypermelanic melanophores were larger and more dendritic in morphology compared to surface fish melanophores. However, hypermelanic melanophores responded normally to melanin-concentrating hormone suggesting darkening stemmed from vision loss, rather than a defect in pigment cell function. Finally, a number of genomic regions were coordinately associated with both reduced vision and increased pigmentation. CONCLUSIONS: This work suggests hypermelanism in hybrid Astyanax results from blindness. This finding provides an alternative explanation for phenotypic effect studies of pigmentation QTL as stemming (at least in part) from environmental, rather than exclusively genetic, interactions between two regressive phenotypes. Further, this analysis reveals persistence of background adaptation in Astyanax. As the eye was lost in cave-dwelling forms, enhanced pigmentation resulted. Given the extreme cave environment, which is often devoid of nutrition, enhanced pigmentation may impose an energetic cost. Such an energetic cost would be selected against, as a means of energy conservation. Thus, the pleiotropic interaction between vision loss and pigmentation may reveal an additional selective pressure favoring the loss of pigmentation in cave-dwelling animals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0716-y) contains supplementary material, which is available to authorized users.